CURRICULUM MANAGEMENT IN THE ESTABLISHMENT OF RELIGIOUS CHARACTER - Amar, Muhammad Fadali (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to find out: 1) To understand curriculum management in improving the religious character of students at MA Nurul Jadid, 2) To understand the implementation of curriculum management in forming the religious character of students at MA Nurul Jadid, 3) To find out the supporting and inhibiting factors of curriculum management in improve the religious character of students at MA Nurul Jadid, This research uses descriptive qualitative analysi